Better reproducibility of 2 and 4 mM blood lactate threshold than inflection points - Nishibata, I.; Sakata, N.; Ogawa, S.; Okumura, M. (Medicine & Science in Sports & Exercise, 1993)
The reproducibility of blood lactate threshold measured on an electrically braked ergometer was evaluated. Lactate threshold was determined as the workload of first inflection point, second inflection point. Measurements at 2 mM and 4 mM levels were also taken. It was found that work capabilities at 2 and 4 mM thresholds were better indices for evaluating training effects than the location of lactate inflection points. Implication: It is better to determine exercise training responses by performance at particular levels of LA concentration than to describe the characteristics of the two inflection points of blood lactate concentrations. However, the practicality of controlling LA levels in field situations is very low. On the other hand, an athlete's perceptions of effort levels and states of fatigue make this orientation more reasonable. It is the athlete that can sense the internal state and so perceived exertion is justified partly by this finding. This study does show that inflection points are not as precise measures of training effects as are standard work task performance changes.